Literary tourism and its role in the study of culture (based on the material of the life and work of Dusan Makovitsky) - Benčič, S.; Kharitonova, L. (KU Publ., 2021)
The article deals with the issues of literary tourism in Slovakia based on the material of the life and work of the personal doctor of the great Russian writer L.N. Tolstoy, the famous Tolstovian, Dusan Makovitsky. The first part contains a theoretical overview of the phenomenon of literary and cultural tourism. The second part of the article examines its advantages in the context of education, and also provides specific examples of destinations with a great tourism potential for admirers and literary researchers of L.N. Tolstoy. Authentic places and artefacts related to the life of L.N. Tolstoy and D. Makovitsky allow expanding knowledge on this topic in such fields of science as history, religious studies, cultural studies, geography, etc. The article presents new ways and opportunities for teaching and studying history, culture and literature within the framework of specific aspects of Russian-Slovak cultural relations, as well as world culture in general.
Əдеби туризм жəне оның мəдениеттанудағы рөлі (Душан Маковицкийдің өмірі мен шығармашылығының негізінде)
Литературный туризм и его роль в изучении культуры (на материале жизни и творчества Душана Маковицкого)
Keywords: literary tourism; L. N. Tolstoy; Dusan Makovitsky; studying history; culture and literature; cultural relations